Repeat ultrasound in pediatric EDs improves appendicitis diagnosis after referral imaging - Perepelitsa, Vitaliy; Ames, Jeffrey; Kaila, Rahul; Sausen, Nicholas; Schneider, Kari; Lunos, Scott; Segura, Bradley; Avendano, Pablo; Louie, Jeffrey P. (Frontiers in Pediatrics, 2025)
BackgroundAcute appendicitis is a leading cause of surgical emergencies in children, with ultrasound (US) emerging as a preferred diagnostic tool due to its lack of radiation and cost-effectiveness. However, the accuracy of US is highly operator-dependent and may vary between general referring emergency departments (EDs) and specialized pediatric EDs.ObjectiveTo compare the diagnostic sensitivity and specificity of US performed at referring EDs vs. a pediatric ED in identifying acute appendicitis.MethodsA retrospective study analyzed pediatric patients aged <18 years who underwent US at referring EDs and were transferred to a pediatric ED for repeat imaging between July 2018 and July 2023. Data collected included US findings, surgical pathology, white blood cell count, and patient disposition. Sensitivities of the US were calculated and compared between settings.ResultsAmong 64 children included, the US at the pediatric ED demonstrated higher sensitivity (85.2%) compared to referring EDs (51.9%) (p = 0.018). Pediatric ED US resulted in fewer non-visualized appendices (a 34.4% reduction) and equivocal findings (a 30.5% reduction). Patients with positive surgical pathology exhibited higher white blood cell counts (mean 17.1) and neutrophil percentages (mean 81.0%). False positive rates were low (6.9%), aligning with published benchmarks.ConclusionUS performed at pediatric EDs exhibited superior diagnostic accuracy for appendicitis compared to referring EDs, likely due to operator expertise and enhanced imaging protocols. Efforts to standardize training and improve resources at referring EDs may reduce diagnostic disparities and unnecessary interventions.